Bioactive Medications for the Delivery of Platelet Derivatives to Skin Wounds - Bonferoni, Maria C.; Rossi, Silvia; Sandri, Giuseppina; Caramella, Carla; Del Fante, Claudia; Perotti, Cesare; Miele, Dalila; Vigani, Barbara; Ferrari, Franca (Current Drug Delivery, 2019)
Chronic wounds are the result of alterations in the complex series of events of physiological wound healing. In particular, the prolonged inflammation results in increased protease activity, in the degradation of extracellular matrix (ECM) and of growth factors (GFs). The relevance of platelet GFs in maintaining and restoring the complex equilibrium of different moments in wound healing is well recognized. Moreover, the observed decrease of their levels in chronic wounds suggested a possible therapeutic role of the external application to the wounds. It has been also pointed out that tissue regeneration can be more efficiently obtained by the synergic use of different GFs. Platelet derivatives such as platelet- rich plasma (PRP) and platelet lysate (PL) are able to release GFs in a balanced pool. Their therapeutic use in regenerative medicine and wound healing has been therefore more and more frequently proposed in clinical trials and in the literature. The development of a suitable formulation able to control the GFs release rate, to protect the GFs, and to assure their prolonged contact with the wound site, is of paramount importance for the therapeutic success. The present review considers some formulation approaches for PRP and PL application to wounds.
Keywords: platelet lysate